2001
DOI: 10.1055/s-0037-1616144
|View full text |Cite
|
Sign up to set email alerts
|

Factor IX Denver, ASN 346→ASP Mutation Resulting in a Dysfunctional Protein with Defective Factor VIIIa Interaction

Abstract: SummaryHemophilia B is a sex-linked recessive bleeding disorder characterized by the presence of either a decreased amount of normal factor IX (FIX) or the presence of a dysfunctional FIX. We have identified a unique mutation in a family with mild hemophilia B. DNA analysis of family members revealed a single base transition in the 8th exon of the FIX gene predicting an amino acid change of Asn 346→Asp in the catalytic domain. The FIX variant, named FIX Denver, was purified from proband plasma. Kinetic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The FIX‐Met394Thr variant is immediately adjacent to loop 386–393, which may affect this interaction. A previous study reported that the FIX‐Asn393 (346) Asp variant caused a significant decrease in FIXa and FVIIa affinity (Lefkowitz et al, 2001). The FIX‐Met394Thr variant is adjacent to this variant site and may cause HB due to impaired interaction with FVIIa.…”
Section: Discussionmentioning
confidence: 99%
“…The FIX‐Met394Thr variant is immediately adjacent to loop 386–393, which may affect this interaction. A previous study reported that the FIX‐Asn393 (346) Asp variant caused a significant decrease in FIXa and FVIIa affinity (Lefkowitz et al, 2001). The FIX‐Met394Thr variant is adjacent to this variant site and may cause HB due to impaired interaction with FVIIa.…”
Section: Discussionmentioning
confidence: 99%